2014
DOI: 10.1021/bi500868g
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Mitochondrial Membrane Phospholipid Content Lowers the Enzymatic Activity of Electron Transport Complexes

Abstract: Activities of the enzymes involved in cellular respiration are markedly influenced by the composition of the phospholipid environment of the inner mitochondrial membrane. Contrary to previous suppositions, we show that fusion of mitochondria isolated from healthy cardiac muscle with cardiolipin or dioleoylphosphatidylcholine results in a 2-6-fold reduction in the activity of complexes I, II, and IV. The activity of complex III was unaffected by increased phospholipid levels. Phospholipid content had an indiscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(24 reference statements)
0
25
0
1
Order By: Relevance
“…In this regard experiments designed to test the role of certain phospholipids on function have utilized isolated organelles, such as mitochondria, and to these isolates have been added specific glycerolphospholipids to test the effects of MLR. For example, Shaikh et al [52] prepared small PC vesicles or PC/cardiolipin vesicles and incubated these with isolated, suspended rat heart mitochondria in vitro. The vesicles were observed to fuse with the mitochondria, resulting in reductions in electron transport enzymatic activities.…”
Section: Membrane Lipid Replacement-in Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard experiments designed to test the role of certain phospholipids on function have utilized isolated organelles, such as mitochondria, and to these isolates have been added specific glycerolphospholipids to test the effects of MLR. For example, Shaikh et al [52] prepared small PC vesicles or PC/cardiolipin vesicles and incubated these with isolated, suspended rat heart mitochondria in vitro. The vesicles were observed to fuse with the mitochondria, resulting in reductions in electron transport enzymatic activities.…”
Section: Membrane Lipid Replacement-in Vitro Studiesmentioning
confidence: 99%
“…The vesicles were observed to fuse with the mitochondria, resulting in reductions in electron transport enzymatic activities. Thus the authors concluded that increasing mitochondrial membrane phospholipid content lowers electron transport enzymatic activities [52]. There are a number of problems with this approach, including the misinterpretation that this in vitro experiment is the same as MLR.…”
Section: Membrane Lipid Replacement-in Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of CTα is also embryonically lethal [27], whereas loss of CTÎČ results in viable mice with no apparent effect on skeletal muscle phenotype [28]. Excess membrane PC also appears to have detrimental effects on mitochondria, as fusing unilamellar vesicles composed of dioleoyl-PC to mitochondria from cardiac muscle increases PC content and reduces ETS complex I, II, and IV activity [29]. Together, these observations highlight the functional importance of PC in regulating skeletal muscle mitochondrial function.…”
Section: Phosphatidylcholinementioning
confidence: 99%
“…CL acyl chain composition, in addition to its content, is also relevant for regulating the packing properties of phospholipids and potentially influencing protein activity [24,25]. Phospholipids such as phosphatidylethanolamine (PE) and phosphatidylcholine (PC) also have an influential role in mitochondrial function, although they are significantly less studied compared to CL.…”
Section: Introductionmentioning
confidence: 99%